2021
DOI: 10.21203/rs.3.rs-588275/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Associations Between Personality Traits and Adherence to Treatment in Patients with Primary Open Angle Glaucoma in an African Population

Abstract: Purpose: There is poor adherence to medication among patients with glaucoma especially in people of African ancestry. The present study assessed the influence of personality traits on adherence to glaucoma medication among patients living with primary open angle glaucoma (POAG) from an African population. Methods: A clinic-based cross sectional study was conducted among patients with POAG attending a specialist eye care facility. Adapted and validated personality trait and medication adherence measures questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…They experience generally negative emotions which can lead to poor adherence to medications. This is the case of most studies such as a systematic review done in India (15) and a cross-sectional study done Ghana (27). However a study done in Italy using the short version of Big Five Inventory ( BFI-10) to assess personality traits has found that conscientiousness was also associated with lower level of adherence to medication (14).…”
Section: Discussionmentioning
confidence: 99%
“…They experience generally negative emotions which can lead to poor adherence to medications. This is the case of most studies such as a systematic review done in India (15) and a cross-sectional study done Ghana (27). However a study done in Italy using the short version of Big Five Inventory ( BFI-10) to assess personality traits has found that conscientiousness was also associated with lower level of adherence to medication (14).…”
Section: Discussionmentioning
confidence: 99%